Towards Renewable Energy: Awareness and Acceptance of Mini Independent Power Producers in Kota Kinabalu Sabah - Mariati, Jaafar; Azhaili, Baharun (2025)
The rising energy demand has drawn significant focus towards sustainable energy sources. As Sabah, being rich in renewable energy resources, presents significant potential in this regard a survey was conducted among 264 residents of Kota Kinabalu, Sabah, to assess their awareness and acceptance of renewable energy and their willingness to become mini independent power producers. The data obtained from study were analysed using SPSS 27 statistical software package. The findings reveal a high level of awareness of renewable energy among residents, alongside a strong acceptance of the concept of becoming mini-independent power producers, regardless of income groups. These results highlight a positive outlook for renewable energy adoption in Kota Kinabalu. This study offers valuable insights for policymakers to further promote and implement solar energy initiatives in Kota Kinabalu, Sabah.